The evolution of the Antarctic Treaty System: a structure and dynamics of the acts adopted for 1961-2011 - Fedchuk, A. (Ukrainian Antarctic Journal, 2012)
This article gives an overview of the international-political preconditions and specific development of the governmental regime based on the Antarctic Treaty of 1959 and knowing as the Antarctic Treaty System (ATS). The structure and dynamics of all political acts are analyzed (such as conventions, protocol, agreed measures, decisions, resolutions and recommendations as well), which were adopted during all regular and special meetings within the ATS for 1961-2011. The topical issues for each decade were indicated: the 1960s – ensuring information exchange and entering into inter-national scientific cooperation; the 1970s – the prospect of exploration and exploitation of natural researches in the Antarctic region. The 1980s was the most complex and dynamic period in the history of the Antarctic governance. Four parallel developments were characterized of the ATS for that period as the following: the intensifying debate among the Consultative Parties within the ATS; the attack on the ATS by a group of developing countries which were outside the ATS; the increasing support for the ATS from countries outside the ATS and achieving a member status; and the growing concern about the conservation of Antarctica, initiated by the environmental movement. This last development became the dominant in the future 1990s. The acts in the 2000s were adopted in order to strengthen and to institualizate the ATS as well as to anticipate its new challenges such as invasion of non-native species, organization human activities with a glance of natural changes in Antarctic ecosystems due to global and regional climate warming; and regulating commercial activities. First of all, the attention should be paid on Antarctic tourism and bioprospecting. In spite of developmental character of the ATS two short and critical periods of bifurcation were indicated with 30-years interval. The first one (1959-1961) ended when Antarctic Treaty entered into force. It was a real success of international diplomacy as international conflicts were turned into stability and effective co-operation. The second one ended with adoption of the Protocol on environmental protection. Consequently Antarctica as a potential region of mining was turned into natural reserve devoted to piece and science. The estimated third bifurcation point will be in 2041, because of Environmental Protocol expiry as well as actualization the sovereignty claims and delimitation of continental shelf in the South ocean.